Achieving Ambitious Positions in Multilateral Chemicals Negotiations: How does the European Union influence the Negotiation Outcomes? - Frauke Pipart (Journal of Contemporary European Research, 2022)
This paper explains the influence of the European Union (EU) in multilateral chemicals negotiations. Focusing on the Basel Convention, this paper studies two issues negotiated at the Conference of the Parties 2019. Comparing a success and a failure case for the EU, it provides explanations for the EU’s high influence in the negotiations on the management of plastic waste and its low influence in the negotiations on low Persistent Organic Pollutant content values. Using process-tracing, the paper maps the EU’s diplomatic activities from the EU’s initial position to the outcome of the negotiations. Two separate causal mechanisms outline the differences between the success and the failure of the EU. Data is collected through interviews, observations and official documents. The paper shows the crucial role of the EU’s diplomatic activities in multilateral negotiations. The EU can be influential, if it strongly engages in all negotiation forums, is able to adapt its position during the course of negotiations and can propose a compromise acceptable to all parties. It is however uninfluential, if it downscales its diplomatic activities and refuses to compromise.